What money can't buy: allocations with priority lists, lotteries and queues - Daniele Condorelli (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2009)
I study the welfare optimal allocation of a number of identical and indivisible objects to a set of heterogeneous risk-neutral agents under the hypothesis that money is not available. Agents have independent private values, which represent the maximum time that they are willing to wait in line to obtain a good. A priority list, which ranks agents according to their expected values, is optimal when hazard rates of the distributions of values are increasing. Queues, which allocates the object to those who wait in line the longest, are optimal in a symmetric setting with decreasing hazard rates.
Keywords: D45; D82; H42; 330; rationing; queues; priority lists; lotteries